The Relationship Between Knowledge Level and Social Media Use with Participation in the COVID-19 Vaccination Program in Pangkalan Kerinci Urban Village - Fitri Salwa Huriani; Lili Irawati; Hardisman; Rosfita Rasyid; Biomechy Oktomalio Putri (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: COVID-19 vaccination represents a crucial public health strategy for controlling viral transmission by inducing protective immunity and reducing the severity of symptoms. Knowledge levels and social media exposure are among the factors that may influence individuals’ willingness to participate in vaccination programs. This study aimed to analyze the relationships between knowledge level, social media use, and community participation in the COVID-19 vaccination program in Pangkalan Kerinci Kota Urban Village. Methods: An analytic, cross-sectional design was employed involving 106 residents aged 17–65 years selected through proportionate stratified random sampling and consecutive recruitment. Data were analyzed using the Chi-square test. Results:Most respondents demonstrated good knowledge regarding COVID-19 vaccination and reported frequent use of social media platforms. Statistical analysis revealed no significant relationship between knowledge level and participation in the vaccination program (p = 0.610) or between social media use and vaccination participation (p = 0.302). Discussion:The absence of significant associations suggests that vaccination uptake in this population may be influenced more strongly by structural or contextual factors, such as access to health services, trust in local authorities, and availability of vaccination sites, rather than by cognitive understanding or social media exposure alone. High knowledge levels and active social media use do not necessarily translate into health-seeking behavior, indicating a possible gap between awareness and action. Future studies should explore additional determinants, including perception of risk, cultural influences, and policy-driven motivators. Conclusion: Knowledge level and social media use were not significantly associated with participation in the COVID-19 vaccination program in Pangkalan Kerinci Kota Urban Village.